Janus-Faced Neutrophil Extracellular Traps in Periodontitis - Vitkov, Ljubomir; Hartl, Dominik; Minnich, Bernd; Hannig, Matthias (Frontiers in Immunology, 2017)
Periodontitis is characterized by PMN infiltration and formation of neutrophil extracellular traps (NETs). However, their functional role for periodontal health remains complex and partially understood. The main function of NETs appears to be evacuation of dental plaque pathogen-associated molecular patterns. The inability to produce NETs is concomitant with aggressive periodontitis. But in cases with exaggerated NET production, NETs are unable to maintain periodontal health and bystander damages occur. This pathology can be also demonstrated in animal models using lipopolysaccharide as PMN activator. The progress of periodontitis appears to be a consequence of the formation of gingival pockets obstructing the evacuation of both pathogen-associated and damage-associated molecular patterns, which are responsible for the self-perpetuation of inflammation. Thus, besides the pathogenic effects of the periodontal bacteria, the dysregulation of PMN activation appears to play a main role in the periodontal pathology. Consequently, modulation of PMN activation might be a useful approach to periodontal therapy.